Cellulase-Assisted Enhancement of Phenolics in Black Glutinous Rice Tape: An RSM Optimization Study - Subando, Teresa Ramadhinara; Swasti, Yuliana Reni; Putra, Venansius Galih Perkasa (Diponegoro University, 2025)
Black glutinous rice (BGR) tape is a traditional fermented product rich in phenolic compounds, which may provide health benefits. However, the dense aleurone layer and limited microbial activity during fermentation may leave a portion of bound phenolics. This study aimed to maximize the total phenolic content (TPC) in BGR tape by combining cellulase treatment with statistical optimization. Using response surface methodology (RSM), a two-factor central composite design (CCD) was employed to evaluate the effects of incubation time and enzyme concentration on TPC response (Folin-Ciocalteu, mg GAE/g sample). A quadratic model was developed and assessed through analysis of variance (ANOVA) and diagnostics. The ANOVA results indicated the model was significant, and the lack-of-fit was not significant. The findings showed that the most influential variables were the linear term of incubation time (p = 0.0001), followed by the quadratic term of incubation time (p = 0.01667), and then the linear term of enzyme concentration. The quadratic term of enzyme concentration and the interaction between factors had no significant effect. Response surface and contour plots revealed that longer incubation times increased TPC, though extended incubation eventually led to a decrease. RSM analysis identified an optimal fermentation time of 71.16 h and an enzyme concentration of 21.13 U/g of enzyme, predicting a TPC of 0.414 mg GAE/g with a desirability of 1. These results suggest that the optimal condition for optimizing TPC in BGR tape involves extended incubation periods and low to moderate enzyme concentrations. The model provides a quantitative basis for process optimization within the studied ranges. Overall, RSM proves to be an effective method for optimizing phenolic enhancement in BGR tape fermentation.